Dynamic Language Use in Bi/Multilingual Early Childhood Education Contexts - Ryan W Pontier (Journal of Culture and Values in Education, 2020)
The population of bilingual students learning and using more than one language in the United States has more than doubled in the past 30 years. This is especially true in early childhood, which makes it crucial that educators of young emergent bilingual children understand and support these young children’s bi/multilingual development, including critically understanding the implication of adopting different perspectives of bi/multilingualism. Although much is known about classroom practices in support of emergent bilingual children in Kindergarten and beyond, little is known about those practices in the early years. This article provides a systematic review of relevant empirical studies that investigated teachers’ and children’s dynamic language use in bi/multilingual early childhood education settings. The authors identify several strategic languaging practices enacted by both teachers and children, and strategies for fostering these practices; as well as ways in which teachers leveraged their agency through their languaging practices. Implications for future research, practice, professional development, and policy are discussed.